Manajemen Sumber Daya Manusia dalam Konteks Pendidikan Era Society 5.0 dan Implementasi Kurikulum Merdeka - Siti Karimah, Iim; Hendriani, Ani; Wahid, Rahman; Suryadi, Yadi; Hendrawan, Budi (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2024)
This article discusses human resource management (HRM) in education in the Era of Society 5.0 and the implementation of the Merdeka Curriculum in Indonesia. The Era Society 5.0, which integrates advanced technology with social life, demands adaptive, innovative, and tech-savvy education human resources. Meanwhile, the Merdeka Curriculum gives more freedom to schools and teachers to design learning that suits students' needs. This article analyses how HR management should be adjusted to support these two major changes, including strategies for developing teacher competencies, the use of technology in education management, as well as education quality assurance focusing on 21st century skills. The data sources come from scientific articles, books and other relevant documents. The results show that effective HR management can be the key to improving the quality of education and the readiness of students to face global challenges in the Society 5.0 Era